The Study of Payment Compliance of Independent Workers of National Health Insurance in BPJS Kesehatan Branch Office Ungaran - Beatrik Yosephine Sitorus; Harry Soesanto; Amie Kusumawardhani (Diponegoro Journal of Economics, 2020)
BPJS Kesehatan prove the presence of the country in the welfare of the community, especially in the field of health, and also become evidence for the community to improve the welfare of the lives of the people. But on his journey BPJS Kesehatan has difficulties health financing where one of them is the impact of lack of awareness and compliance of participants, especially the independent worker participants in making dues payments sustainably. The object of this research is the independent workers registered in Ungaran branch office. The analysis used in this research is Structural Equation Modelling (SEM). The invention of this research is the customer experience positively influence the perception of service quality, customer experience positively influences the ease of making payments, perception of service quality positive effect on compliance with payments, ease of payment is positively influential on compliance with payments, and ability to pay has no effect on compliance with payments.